HOW ONESIMUS WAS HEARD – EVENTUALLY. SOME INSIGHTS FROM THE HISTORY OF INTERPRETATION OF PAUL’S LETTER TO PHILEMON - D.F. Tolmie (Acta Theologica)
Although Onesimus is the reason for Paul’s Letter to Philemon, he is only mentioned by name for the first time nearly halfway through the letter (v. 10). He also remains voiceless throughout the letter. This contribution focuses on the history of interpretation of the letter, and, in particular, the way in which the role of Onesimus has been interpreted through the centuries. Several examples of the way in which scholars interpreted the role of Onesimus are discussed, and it is argued that four broad trends may be discerned: Onesimus as a culprit who was saved by Paul; Onesimus as a pawn in the abolitionism debate; Onesimus’ status disputed, and Onesimus as a victim, with the letter being read in a resistant way.